Pelayanan Elektronik dan Keputusan Berwisata: Studi Pada Obyek Pariwisata Edukasi Museum - Muhamad Guntar Suryaatmaja; Dede Jajang Suyaman (Islamic University of Kalimantan MAB Banjarmasin, 2021)
Tourism is one of the strengths in accelerating and supporting regional profitable improvement. The purpose of this study was to determine whether the parties involved in realizing the decision to visit tourist thourgh tourism services. This research is quantitative research conducted using quantitative methods and data collection techniques are carried out through observation, interviews, and recording literartur to managers and tourists in the tourist attraction of the central jawa ranggawarsita museum. The results of testing the product mix coefficient and the decision to visit show the value of t count > t table (10.591>1.661), so Ho is rejected, indicating that there is a significant influence between the product mix and the decision to visit tourists in the central java museum ranggawarsita thus the hypothesis is answered from the research on the effect of the museum product mix on the decision to visit tourists at the ranggawarsita central java museum. The manager of a tourist attraction requires efforts to increase the accesibility and facilities contained in these tourist objects, so that tourists feel comfortable, considering that tourists are one of the sources of income for the community.Keywords: E-Commerce and decisions visiting